Communication in single-and two-parent families and their influence on portuguese and spanish adolescents’ life satisfaction - Camacho, Inês (2018)
Aim: The aim of this study was to analyse the influence of family type on communication with parents and family, as well as to analyse the contribution of communication in single- and twoparents families to adolescent life satisfaction in Portugal and Spain. Methodology: Participants were 5005 Portuguese and 21,423 Spanish adolescents aged 11–16 years, from the 2014 edition of the Health Behaviour in School-aged Children study in Portugal and Spain. Results: Results showed that communication with parents and communication with family, in general, were higher in two-parent families than in single-parent families and was relevant to predict adolescent life satisfaction from single- and two-parent families in Portugal and Spain. Conclusion: The results prove that communication with family is essential to predict life satisfaction in both countries. It is important to work on improving conditions of family life, as well as to implement programmes that promote better communication between all family members, especially in single-parent families.